Distributed generation and its implications for the utility industry - Sioshansi, Fereidoon P. (Fereidoon Perry). (Amsterdam Academic Press, 2014)
Distributed Generation and its Implications for the Utility Industry examines the current state of the electric supply industry; the upstream and downstream of the meter; the various technological, business, and regulatory strategies; and case studies that look at a number of projects that put new models into practice. A number of powerful trends are beginning to affect the fundamentals of the electric utility business as we know it. Recent developments have led to a fundamental re-thinking of the electric supply industry and its traditional method of measuring consumption on a volumetric basis. These developments include decreasing electricity demand growth; the rising cost of fossil fuels and its impact on electricity costs; investment in energy efficiency; increasing numbers of prosumers who generate for some or all of their own needs; and market reforms. This book examines the implications of these trends in chapters focusing on distributed and decentralized generation, transactive energy, the role of electric vehicles, any much more.--P
Electronic reproduction.
Keywords: Distributed generation of electric power; Electric utilities; Electronic books